Fibrin Network Structure: Modification by Platelets - Dhall, T Z; Shah, G A; Ferguson, I A; Dhall, D P (Thrombosis and Haemostasis, 1983)
Platelets play a fundamental role in haemostasis and thrombosis. They are known to undergo characteristic changes including release of subcellular material during clotting. The effect of subcellular platelet material on fibrin network structure, however, has not previously been investigated. Using opacity ratio, syneresis, permeation and electron microscopy it was found that subcellular platelet material extracted into NaCl is able to influence fibrin network structure of clots made from purified fibrinogen as well as platelet-poor plasma. Such clots had higher opacity ratio, reduced syneresis and lower permeability than control clots. Further, the responsible platelet material is heat labile and is released from the platelets during their aggregation with several common aggregating agents. Morphometric analysis of transmission electron micrographs has shown that fibrin fibres in plasma clots made in the presence of platelet subcellular material are thinner than those in control clots. In addition, plasma clots made in the presence of platelet extract had a higher resistance to fibrinolytic digestion than control clots. Thus, platelets play a hitherto undescribed role in regulating fibrin network structure.
Keywords: Platelets; Fibrin network structure; Fibrinolysis